Eksplorasi Nilai-Nilai Budaya dalam Pembelajaran Karakter dan Moral Anak di TK Bukit Permai 2 - Febriani, A.Nurul; Amriani, Sri Rika; Musi, Muhammad Akil (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
The focus of this research is how local cultural values are integrated into character and moral education for children at TK Bukit Permai 2. This study employs a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The validity of the data is tested through triangulation of time, technique, and source, as well as collection, condensation, presentation, and conclusion drawing. The research results show that TK Bukit Permai 2 consistently integrates local cultural values into children's daily activities, such as the use of polite language (